Legal Foundations of International Cooperation in Higher Education in Ukraine and the Role of Administrative and Legal Norms (Bulletin of Kharkiv National University of Internal Affairs, 2025)
The study is devoted to examining the structure of the legal framework for international cooperation in higher education in Ukraine and the place of administrative and legal norms therein by conducting a systematic review of the domestic and international regulatory framework for international cooperation in higher education and identifying key regulatory and legal acts.International cooperation is an integral part of the higher education system and state policy in the field of higher education. The relevance of the study is determined by a number of factors. In particular, the significant role of international cooperation in higher education in attracting investment, post-war reconstruction, solving humanitarian problems, sustainable development of education, science, technology and innovation, as well as their transfer. In addition, despite the existence of a wide range of domestic and international normative legal acts that define both individual and complex components of the relevant legal relations, the study of this topic is characterised by a predominant focus on certain aspects of such cooperation in the context of economic development, education, public administration, etc., while there is a lack of comprehensive studies of the domestic regulatory framework.The international legal framework includes: international legal acts ratified by Ukraine, agreements and treaties on cooperation between various subjects of international cooperation (states, authorities, enterprises, institutions, organisations, individuals, etc.) in the field of higher education, as well as supporting and founding documents of foreign subjects of international cooperation.The relevant domestic regulatory framework consists of the Constitution of Ukraine, laws (of a general and special nature), subordinate regulatory acts (of a regulatory and founding nature), as well as internal regulatory documents on international cooperation between enterprises, institutions and organisations in the field of higher education.